Digital Faith Formation and Christian Religious Education Teachers’ Leadership in 21st-Century Learning - Maranatha, Christian Ade; Tandana, Ester Agustini (Perkumpulan Teolog Agama Kristen Indonesia, 2025)
The rapid integration of digital technology in education has transformed how faith is taught and experienced in Christian contexts. This shift challenges Christian Religious Education (CRE) teachers to maintain theological integrity while engaging learners in online and hybrid spaces. Traditional models of discipleship must now coexist with virtual practices of learning and community building, requiring teachers to navigate the tension between spiritual authenticity and digital innovation. As education in the 21st century emphasizes creativity, collaboration, and critical thinking, Christian educators must also redefine their leadership as a calling that unites faith, ethics, and pedagogy. This transformation positions teachers not merely as instructors but as spiritual mentors who embody servant and transformative leadership within digital learning environments. The purpose of this study is to develop a theological and pedagogical framework for digital faith formation and teacher leadership in contemporary Christian education. Employing a qualitative theological method and literature-based analysis, the research draws from biblical principles and scholarly works in theology, education, and digital pedagogy. Findings show that faith formation in digital contexts must remain relational, participatory, and grounded in the incarnational model of Christ. Effective leadership integrates humility, moral integrity, and technological discernment to sustain authentic spiritual growth. The study contributes by bridging theology and pedagogy, offering a holistic model for spiritually grounded and digitally competent Christian educators in the 21st century. Contribution: This study contributes to contemporary Christian education by formulating an integrative framework that unites theology, pedagogy, and digital literacy, positioning Christian educators as transformative spiritual leaders who cultivate faith, ethics, and relational depth within digital learning communities. Integrasi teknologi digital yang berlangsung pesat dalam dunia pendidikan telah mengubah cara iman diajarkan dan dihayati dalam konteks Kristen. Pergeseran ini menantang para guru Pendidikan Agama Kristen (PAK) untuk tetap menjaga integritas teologis sambil melibatkan peserta didik di ruang pembelajaran daring dan hibrida. Model pemuridan tradisional kini harus berdampingan dengan praktik pembelajaran dan pembentukan komunitas secara virtual, menuntut para pendidik untuk menavigasi ketegangan antara keotentikan spiritual dan inovasi digital. Ketika pendidikan abad ke-21 menekankan kreativitas, kolaborasi, dan berpikir kritis, para pendidik Kristen juga perlu mendefinisikan kembali kepemimpinan mereka sebagai panggilan yang mempersatukan iman, etika, dan pedagogi. Transformasi ini menempatkan guru bukan sekadar sebagai pengajar, melainkan sebagai mentor rohani yang menghidupi kepemimpinan melayani dan transformatif dalam konteks pembelajaran digital. Tujuan penelitian ini adalah mengembangkan kerangka teologis dan pedagogis untuk pembentukan iman digital serta kepemimpinan guru dalam pendidikan Kristen kontemporer. Dengan menggunakan metode teologis kualitatif dan analisis berbasis literatur, penelitian ini berlandaskan pada prinsip-prinsip biblika serta kajian ilmiah dalam bidang teologi, pendidikan, dan pedagogi digital. Hasil penelitian menunjukkan bahwa pembentukan iman dalam konteks digital harus tetap bersifat relasional, partisipatif, dan berakar pada model inkarnasional Kristus. Kepemimpinan yang efektif mengintegrasikan kerendahan hati, integritas moral, dan kepekaan terhadap teknologi untuk menopang pertumbuhan rohani yang otentik. Studi ini memberikan kontribusi dengan menjembatani teologi dan pedagogi, menawarkan model holistik bagi para pendidik Kristen abad ke-21 yang berakar pada spiritualitas Kristen dan kompeten secara digital. Kontribusi: Penelitian ini memperkaya pendidikan Kristen dengan mengintegrasikan teologi, pedagogi, dan literasi digital ke dalam satu kerangka utuh yang memberdayakan pendidik Kristen sebagai pemimpin rohani dalam konteks pembelajaran digital.